Comparison of Functional Outcomes Between Arthroscopic and Open Tenodesis in the Management of Biceps Long Head Tendonitis - Al-Sabti, Mohammed Hatem Salal; Al-Saad, Majed Aswad; Al-Samaraee, Osama Luay (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2025)
Background: Arthroscopic suprapectoral biceps tenodesis (ABT) and open subpectoral biceps tenodesis (OBT) are utilized for treating long head biceps tendon (LHBT) pathology. The clinical advantage of one approach over the other is not well characterized. Objective: To compare arthroscopic tenodesis and open subcortical techniques concerning their functional outcome. Methods: The study included 20 patients aged 20-40 years with long head biceps tendonitis not responding to conservative management. They were randomly allocated into two groups of 10 each. Group 1 received open tenodesis, and group 2 received arthroscopic tenodesis. The outcome was measured, and each case was followed for 1 year based on the American Shoulder and Elbow Surgeons scoring system. Results: The mean ASES score of the open group at 3-month post-operation was 86.7, which did not significantly differ from that of the arthroscopic group (89.5). The mean score 6 months post-operation in the open group was 90.1, which was also not significantly different compared to the arthroscopic group (89.5). Meanwhile, the mean score of the open group after 1 year was 91.1, which was not significantly different from that of the arthroscopic group (91.3). Conclusions: Patients undergoing both procedures experienced similar improvement in the clinical outcomes, without differences regarding treatment failure and functional performance. The arthroscopic group showed increased incidence of residual pain in the early postoperative period.